Dorsal ulnar cutaneous nerve conduction: reference values - Solange G. Garibaldi; Anamarli Nucci (Arquivos de Neuro-Psiquiatria)
We investigated the reference values of the dorsal ulnar cutaneous nerve (DUC) sensory nerve conduction (SNC) in 66 healthy individuals. Measurements were processed using stimulating electrodes positioned between the ulnar bone and the flexor carpi ulnaris muscle, 11-13 cm proximal to the active electrode recording. Superficial recording electrodes were placed on the fourth intermetacarpal space. The mean sensory conduction velocity (SCV) in males was 63.7 -- 0.16 x age ± 3.36 m/s and in females was 57.7 ± 3.37 m/s. The mean sensory nerve action potential (SNAP) amplitude in males was 19.5 ± 10.7 µV and in females was 24.6 ± 5.8 µV. The mean SNAP duration was 0.96 ± 0.13 ms. No significant differences regarding the DUC-SCV, distal latency, and SNAP duration or amplitude were found between both sides of the same subject. The amplitude of the SNAP was higher in females than males. The effects of age on DUC-SCV were distinct for each gender.